Prevalence and Correlates of Active Amphetamine-Type Stimulant Use Among Female Sex Workers in Malaysia - Pedersen, Courtney J.; Wickersham, Jeffrey A.; Altice, Frederick L.; Kamarulzaman, Adeeba; Khoshnood, Kaveh; Gibson, Britton A.; Khati, Antoine; Maviglia, Francesca; Shrestha, Roman (Frontiers in Psychiatry, 2022)
The use of amphetamine-type stimulants (ATS) has been associated with increased sexual risk behaviors and HIV transmission, among other adverse health outcomes. However, ATS use among female sex workers (FSWs) in Malaysia has not yet been characterized. We examined the prevalence and correlates associated with ATS use among Malaysian FSW. Between February and December 2016, 492 FSWs, including cisgender (n=299) and transgender (n=193) women, were recruited using respondent-driven sampling in Greater Kuala Lumpur, Malaysia. A structured questionnaire was used to collect demographic characteristics, sexual behaviors, ATS and other substance use, behavioral health issues, involvement in criminal justice, and experience of physical and sexual trauma. Logistic regression analyses were conducted to determine factors associated with active ATS use, defined as ATS use in the last 30 days. Nearly one-third (32.3%) of participants reported active ATS use. In the multivariable model, ATS use was associated with drug use during sex work (aOR=17.10; 8.32-35.15), having moderate to severe level of substance use disorder (aOR=3.38; 1.48-7.70), and engaging in sex work with multiple clients per day (two clients: aOR=3.39; 1.36-8.46; three clients: aOR=5.06; 1.81-14.10). A high prevalence of ATS use was documented in our sample. The presence of moderate to severe substance use disorder, the use of drugs during sex work activity, and having multiple sex work clients per day were significantly associated with active ATS use. Given these findings, prevention and harm reduction strategies need to be tailored to address the increasing ATS use and the associated adverse health consequences among FSWs in Malaysia.